Bureaucratic politics and foreign policy - Halperin, Morton H. (Brookings Institution Press, 2006)
"Analyzes the role played by the federal bureaucracy--civilian career officials, political appointees, and military officers--and Congress in formulating U.S. national security policy, illustrating how bureaucratic maneuvering influences policy decisions and our international relations"--Provided by publisher.